The Global Financial Crisis : Explaining Cross-Country Differences in the Output Impact - Gelos, R. (IMF Working Papers; Working Paper ;, 2009)
We provide one of the first attempts at explaining the differences in the crisis impact across developing countries and emerging markets. Using cross-country regressions to explain the factors driving growth forecast revisions after the eruption of the global crisis, we find that a small set of variables explain a large share of the variation in growth revisions. Countries with more leveraged domestic financial systems and more rapid credit growth tended to suffer larger downward revisions to their growth outlooks. For emerging markets, this financial channel trumps the trade channel. For a broader set of developing countries, however, the trade channel seems to have mattered, with countries exporting more advanced manufacturing goods more affected than those exporting food. Exchange-rate flexibility clearly helped in buffering the impact of the shock. There is also some -weaker-evidence that countries with a stronger fiscal position prior to the crisis were hit less severely. We find little evidence for the importance of other policy variables.